Corps-dissident, Corps-défendant. Le tatouage, une « peau de résistance » - Emma Viguier (Amnis)
Corporal marks, from the tattoo to the withering, have been used throughout history as a means to stigmatize people, to deprive them of their rights and to exclude them from society. The basis of such treatment in the past has related, and continues to relate, to one’s situation, religion or act : the slave, prisoner, criminal, social misfit, prostitute, enemy of the faith, « non-aryan » of the Nazi ideology. In so-called primitive societies the mark inscribed on the body of the subject comes with its rites of passage, an initiation into a community. Western culture on the other hand has turned the mark into a sign of marginality, of dissidence, of savagery, of subjugation and of dispossession of any identity, a sign of social death. Nevertheless, there are corporal scripts which display and come to terms with their transgressive or even activist nature. By means of the tattoo the skin expresses itself ; it revolts, it resists. Paralysed by a situation perceived as hostile, gruelling, disgraceful or in a context of suffering, the individual uses his body as an offensive instrument of enunciation, of refusal, but also of survival. The tattoo thus asserts itself as a skin of resistance, both a weapon and an armour.